2017
DOI: 10.1186/s12969-017-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a decision aid for juvenile idiopathic arthritis medication choices

Abstract: BackgroundRandomized trials have demonstrated the efficacy of patient decision aids to facilitate shared decision making in clinical situations with multiple medically reasonable options for treatment. However, little is known about how best to implement these tools into routine clinical practice. In addition, reliable implementation of decision aids has been elusive and spread within pediatrics has been slow. We sought to develop and reliably implement a decision aid for treatment of children with juvenile id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Approaches to minimize the effects of JIA on young people vary widely, and their success is often very personalized to the individual. One study evaluating a decision aid for children with JIA found that the tool had high acceptability but lower efficacy, leading authors to call for more innovative approaches to using decision aids and assessing outcomes among children [12]. A review of mobile phone and tablet apps that support personal management of illness in young people found that apps for diabetes, asthma, and chemotherapy recovery show some impact on monitoring and adherence, but the strength of evidence is weak [13].…”
Section: Introductionmentioning
confidence: 99%
“…Approaches to minimize the effects of JIA on young people vary widely, and their success is often very personalized to the individual. One study evaluating a decision aid for children with JIA found that the tool had high acceptability but lower efficacy, leading authors to call for more innovative approaches to using decision aids and assessing outcomes among children [12]. A review of mobile phone and tablet apps that support personal management of illness in young people found that apps for diabetes, asthma, and chemotherapy recovery show some impact on monitoring and adherence, but the strength of evidence is weak [13].…”
Section: Introductionmentioning
confidence: 99%
“…The research team, which included a pediatric gastroenterologist, developed a semistructured focus group guide based on our prior work 7 9 , 13 , 14 and literature review. The focus group guide was reviewed by a patient consultant using cognitive interviewing techniques and revised based on feedback.…”
Section: Methodsmentioning
confidence: 99%
“…Speci cally, what may account for the positive impacts of frequent interaction between clinicians and staff, and what might these interactions entail? Studies from over two decades of implementation research suggest that implementation success is typically bolstered by having at least one clinician champion to promote the use of a decision support intervention (23,32,(38)(39)(40)(41)(42).…”
Section: The Structural Dimension: Organizational Size Standardizatimentioning
confidence: 99%
“…The critical role of clinician champions has also recently been highlighted by Berry et al (41), who found that designating a clinical lead for implementation helped to address staff misunderstandings about which contexts and resources were best suited for administering decisional support. Brinkman et al (42) likewise found that implementation was facilitated by buy-in from physicians about the value of SDM and formal training workshops for clinical staff implementing decision support. Further, a study by Uy et al (16) similarly identi ed physician support as "crucial" to the distribution success of patient decision supports.…”
Section: The Structural Dimension: Organizational Size Standardizatimentioning
confidence: 99%
See 1 more Smart Citation